DEMOKRASI INDONESIA, MEDIA SOSIAL, DAN PENTINGNYA ETIKA PROFETIK - MANSHUR, FADLIL MUNAWWAR (Tsamratul Fikri | Jurnal Studi Islam, 2018)
This article discusses Indonesian democracy, the existence and development of social media, and the importance of prophetic ethics for all Indonesians. The results of the study confirm that ideal Indonesian democracy can only be realized if every citizen is aware of the roles, responsibilities, and rights and obligations. The effort to realize the ideal of Indonesian democracy will also be largely determined by the ability of the Indonesian people to manage one of the biggest challenges of democracy today, namely the massive and widespread presence and development of social media. The use of social media to play an effective role in building ideal Indonesian democracy needs to be accompanied by prophetic ethical values that are believed to be able to fortify its users from destructive, provocative, manipulative and destructive attitudes and behaviors.